Type 1 Autoimmune Pancreatitis Unmasked by COVID-19 Vaccine. Issue 1 (25th January 2023) - Becker, Erica C.; Siddique, Osama; Kapur, Dinesh; Patel, Krishna; Mehendiratta, Vaibhav
ABSTRACT: Autoimmune pancreatitis is a rare fibro-inflammatory disease with 2 distinct subtypes of which each has their own clinical presentation, risk factors, and histopathological patterns. We present a case of newly diagnosed type 1 autoimmune pancreatitis in a symptomatic 54-year-old man with stable ulcerative colitis 1 month after COVID-19 vaccination. Previous reports have indicated that vaccinations can trigger autoimmune disease in predisposed individuals. This case discusses the occurrence of autoimmune pancreatitis triggered after COVID-19 vaccination.